Synthesis and characterization of Mn-Pt/AC nanoparticles and their photocatalytic and antibacterial applications. Issue 4 (15th March 2022) - Gul, Tamanna; Khan, Idrees; Ali, Sajid; Sadiq, Mohammad; Saeed, Khalid
Abstract: Manganese–platinum oxide nanoparticles/activated carbon nanoparticles (Mn-Pt/AC NPs) and manganese–platinum oxide nanoparticles (Mn-Pt NPs) were synthesized via chemical reduction process and employed for photodegradation of Orange II dye in aqueous medium. scanning electron microscopy (SEM) study illustrated that AC-supported NPs were present in dispersed form while neat NPs are mostly in agglomerated form. The formation of these NPs was also confirmed by EDX and FT-IR. The photodegradation study shows that the Mn-Pt/AC NPs and Mn-Pt NPs degraded 46 and 37% of Orange II, respectively, without using H2 O2 . However, using H2 O2, the dye degradation efficiency of both types of catalysts was increased (more than 90%) due to its high oxidizing ability. The effect of other parameters like catalyst dosage, pH, and dye concentration was also studied. Both Mn-Pt/AC NPs and Mn-Pt NPs showed significant bioactivities against two pathogenic bacteria, that is, Proteus mirabilis and Acinetobacter baumannii . GRAPHICAL ABSTRACT: UF0001